Penguatan Lingkungan Hidup Melalui Pengelolaan Sampah Rumah Tangga di Perum Bukit Pinang Bahari Rt 01 Kelurahan Gunung Panjang - Diepa Febriana Wulandari; Hidayah, Wardatul; Nuzula Elfa Rahma; Wike Pratiwi (Fakultas Teknik Universitas Palangka Raya, 2023)
Poor waste management degrades the quality of the environment. Poor waste management is partly caused by the increasing number of people accompanied by the increasing level of consumption of the population. However, this is not accompanied by an increase in the quality of waste management. This is because a good understanding of waste has not been internalised, that every living person will produce waste every day. This has become one of the focuses of work in community service activities carried out by lecturers of the environmental management study programme. Some of the work programmes carried out in order to foster an understanding of the importance of waste management include a waste sorting socialisation programme and strengthening existing waste banks, as well as a biopore hole making programme. This activity was carried out in a series of service activities for one month which took place in Gunung Panjang Village, precisely in Bukit Pinang Bahari Housing RT 01.